FENOMENA MAHASISWA DALAM MELANJUTKAN PROGRAM PROFESI NERS - Ratna Dewi (HUMAN CARE JOURNAL, 2016)
ABSTRAK Penelitian ini bertujuan untuk mengekplorasi pengalaman mahasiswa ners yang bukan alumni dari S1 Keperawatan Fort De Kock untuk melanjutkan program profesi ners di STIKes Fort De Kock Bukittinggi Tahun 2016. Menggunakan jenis penelitian kualitatif dengan pendekatan fenomenologi, Penelitian ini akan dilakukan di STIKes Fort De Kock Bukittinggi pada bulan Desember-Januari 2015. jumlah partisipannya  sebanyak 5 orang dengan pengambilan partisipan menggunakan teknik purposive sampling.Hasil wawancara dianalisa dengan menggunakan metode colaizzi. Hasil wawancara didapatkan tema yaitu 1) Termotivasi  melanjutkan profesi ners di FDK, 2) pengaruh dukungan sosial, 3) sumber informasinya menarik. Fenomena mahasiswa luar untuk melanjutkan pendidikan program profesi diSTIKes Fort De Kock saat ini sangat diminati karena mereka  memilih Fort De Kock  yang sudah memiliki akreditasi yang cukup bagus yaitu B, mereka memilih fort de kock jaga dipengaruhi oleh dukungan keluarga dan teman. Diharapkan program profesi ners di STIKes Fort De Kock bisa lebih baik lagi dan menjadi program profesi ners terbaik di Sumatra Barat.  Kata Kunci : Motivasi, Program Profesi Ners  ABSTRACT This study attempts to the exploration experience of ners students who are not taking bachelor degree of nursing kock to continue their practical in profession ners in in Health Science of fort de Kock Bukittinggi by the year of 2016. This study was used the qualitative approach phenomenology. This research held on Health Science of  fort de kock bukittinggi on December 2015 through January 2016. The number of partisipant in this study was  five people who accaptenced as a participants, taken by using  purposive sampling. The results of interviews were analysed by using colaizzi  method. The results of the interviews obtained the theme such as 1 ) motivated continue profession ners in Fort De Kock Health Science, 2 ) the influence of  social support, 3 ) the sources of the information interesting.  The phenomenon of students out to go education a ners program in fort de kock Health Science currently a very popular as they choose a fort de kock Health Science are having a pretty good accreditation b, they choose a fort de kock Health Science watch influenced by  family and friends support. This study are expected to the ners profession program  in Health Science  fort de kock. It will be even better and become programmed profession ners best in West Sumatera. Eevery year many students nursing who wish to continue profession ners in Fort De Kock Health Science . Keywords: Motivation , The Profession Ners